Cellulose Microfibers from Salacca Midrib Fiber Isolated by the Mechanical Treatment - Venditias Yudha; Ferriawan Yudhanto; Heru Santoso Budi Rochardjo; Satriawan Dini Hariyanto (JURNAL SELULOSA, 2021)
Salacca midrib fibers are abundant natural waste in Turi, Sleman Regency, Daerah Istimewa Yogyakarta. Cellulose Microfibers from the salacca midrib fiber has been isolated by mechanical treatment and successfully has good physical characteristics. Cellulose fibers with micro sizes can strengthen the bond effect between the matrix and the fiber due to the vast contact area. The method for isolated cellulose microfibers by mechanical treatment for speed rotation of 5000, 10000 and 15000 rpm. Mechanical stirrer treatment aims to fibrillation and reduces fiber dimensions because of their high rotation. The characterization by XRD, FTIR, and SEM. The XRD results showed that the mechanical stirrer treatment did not damage the crystallinity index of cellulose microfibers. The crystallinity index of the raw material is 64.3%, increased to 79.1% for the microfiber cellulose crystallinity index. Identification of functional groups using FTIR did not show changes in cellulose compounds resulting from mechanical treatment. Morphological observation of fibers by SEM shows that the diameter cellulose microfibers size obtained from salacca midrib fiber ranges 5-10 µm with 100-300 µm in length. Cellulose microfibers have potential materials as reinforcement in the micro composite and extraction into nanocellulose materials.